2018
DOI: 10.1021/acs.jmedchem.8b00875
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Class A GPCRs: Targets, Agents, and Emerging Concepts

Abstract: G-protein-coupled receptors (GPCRs) have been tractable drug targets for decades with over one-third of currently marketed drugs targeting GPCRs. Of these, the class A GPCR superfamily is highly represented, and continued drug discovery for this family of receptors may provide novel therapeutics for a vast range of diseases. GPCR allosteric modulation is an innovative targeting approach that broadens the available small molecule toolbox and is proving to be a viable drug discovery strategy, as evidenced by rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 280 publications
(630 reference statements)
0
99
0
Order By: Relevance
“…Topological analysis of multiple GPCR structures using computational algorithms revealed a high diversity of the allosteric binding sites as the ligands could locate within the ECLs, between TM helices and within the ICLs (see Figure 4 and [23]). Similarly to other GPCRs [24,25], allosteric modulation of rhodopsin also was suggested [26][27][28][29].…”
Section: Potential Rhodopsin Allosteric Binding Pocketsmentioning
confidence: 81%
See 2 more Smart Citations
“…Topological analysis of multiple GPCR structures using computational algorithms revealed a high diversity of the allosteric binding sites as the ligands could locate within the ECLs, between TM helices and within the ICLs (see Figure 4 and [23]). Similarly to other GPCRs [24,25], allosteric modulation of rhodopsin also was suggested [26][27][28][29].…”
Section: Potential Rhodopsin Allosteric Binding Pocketsmentioning
confidence: 81%
“…(see Figure 4 and [23]). Similarly to other GPCRs [24,25], allosteric modulation of rhodopsin also was suggested [26][27][28][29]. Structural analysis of dark state rhodopsin, its photoactivated Meta II state and opsin suggested that the allosteric sites emerge only after light-induced rearrangement of TM helices within the Meta II and opsin structures and involve either rhodopsin's ICLs or ECLs.…”
Section: Of 18mentioning
confidence: 89%
See 1 more Smart Citation
“…The advantages that these compounds could bring to the clinic have fostered their search, with four of them eventually being approved for clinical use: the positive allosteric modulator of the calcium-sensing receptor cinacalcet used for primary and secondary hyperparathyroidism and severe hypercalcemia; the allosteric antagonist of purinergic P2Y 12 receptor ticagrelor as an anti-thrombotic; the negative allosteric modulator maraviroc for the C-C chemokine CCR 5 receptor; and plerixafor for the C-X-C chemokine CXCR 4 receptor, used for HIV infection and bone marrow transplantation. Many other molecules are currently in clinical trial [ 115 ]. This tremendous progress was made possible by GPCR crystal structures, a variety of functional assays, and in silico computer-based modeling that have improved and optimized the design and development of these drugs.…”
Section: Exogenous Allosteric Modulator Of Dopamine Receptorsmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs) are a superfamily of transmembrane receptors that detect and transmit a large array of extracellular signals (i.e., sensory stimuli, hormones, neurotransmitters), which allow regulating many different physiological functions (i.e., vision, blood pressure, central nervous system activity) [1]. Accordingly, these kinds of receptors represent the main target (~35%) of clinically used drugs [2]. Most GPCR-targeting drugs consist of ligands, either agonists or antagonists, which bind to the endogenous ligand (orthosteric) binding site.…”
Section: Introductionmentioning
confidence: 99%